A descriptive analysis of product quality, price, brand image, and service quality towards customer satisfaction in the Batik Industry - Che Cob, Che Mohd Syaharuddin; Tengku Mohamed Fauzi, Tg Nur Liyana; Abdul Wahab, Mohd Hafeez Al-Amin; Mohd Asdi, Ain Izzati Syamimi; Muhammad, Fatin Nabilah; Adnan, Nur Fatin Syuhada (International Journal of Accounting, Finance and Business, 2025)
This study examines customer satisfaction in the batik industry, focusing on product quality, price, brand image and service quality. Data was collected through surveys of customers of various batik retailers. The descriptive statistics show the mean values of each determinant to provide a comprehensive understanding of their impact on customer satisfaction. Service quality received the highest mean score, followed by brand image, product quality, and the price. This reflects the crucial role of service quality in customer satisfaction. The findings offer valuable implications for batik retailers seeking to increase customer satisfaction by prioritizing improvements in product quality and service offerings. Future research should investigate the dynamic interplay between these determinants and examine how digital marketing strategies can further influence customer satisfaction in the batik industry.